Características do clima de Uberlândia-MG: análise da temperatura, precipitação e umidade relativa - Petrucci, Eduardo (2018)
The objective of this work is to analyze the behavior of the varying temperatures, relative humidity and precipitation of the city of Uberlândia / MG. Daily data of these variables were used, recorded by the Uberlândia Conventional Weather Station, No. 83.257. In the initial steps, the data were organized and tabulated, with validation and filling in of the faults realized. Subsequently, a descriptive statistical analysis was performed: monthly, annual and quinquennial values of the mean temperature (maximum, average and minimum), maximum temperature (absolute maximum and average), minimum temperature (absolute minimum and average), relative humidity (maximum and average) and minimum relative humidity (minimum and average), and the maximum in 24 hours and total annual precipitation. Frequency analysis using the Permanence Curve method allowed the identification of inter-quinquennial variations. In the distribution of rainfall probabilities and construction of the I-D-F curves and the Intense Rainfall Equation for the city, the data were adjusted with Gumbel’s probability density function. The results indicate that there are positive trends (increase) in absolute maximum temperature values, with a mean of 35.9 ° C and a amplitude of 3.1 ° C, and mean values of the 1980s, 34.4 ° C, 1990, 35.5 ° C, 2000, 36.1 ° C and 2010 with 37.5 ° C; Minimum temperature, with a mean temperature of this period of 7.3 ° C and amplitude of 3.6°, and mean values of the 1980s , 5.4 ° C, 1990, 6.7 ° C, 2000, 7.9 ° C, and 2010 with 9°C; Mean temperature, with a mean in this period of 22,6°C and a amplitude of 1,4°C, and mean values of the 1980s, 22°C, 1990, 22,6°C, 2000, 22,8°C and 2010 with 23,4°C. Negative trend (reduction) in the values of Minimum Relative Humidity, with an average of 34% and amplitude of 10.8%, and average values of the 1980s with 39.6%, 1990 with 34.4%, 2000 with 32,4% and 2010 with 28.8%; Maximum Relative Humidity with a sensitive reduction of 1.1%; and Average Relative Humidity, with mean of 68% and amplitude of 5%, average values of the 1980s with 70%, 1990 with 69%, 2000 with 68% and 2010 with 65%. Concerning precipitation, in the last years rainfall has been registered below the average of the historical period that is of 1487 mm, and mean values of the decades of 1980 of 1593 mm, 1990 with 1490 mm, 2000 with 1560 mm and 2010 with 1269 mm. From the decade of 2010 the sequences of days without rainfall in the rainy season and sequences of days without rainfall were intensified. From the calculation of the intense rainfall equation and IDF curves, the values of the regression constant "a" = 330.4083, regression coefficient "b" 0.1452 and mean of the regression coefficients for all returns "c" "C = -0.6164, resulting in the Intense Rainfall Equation: I = (330.4083 x T0.1452) / t0.6164. Through the I-D-F graph, more intense rains are expected in the first few hours of duration for periods of longer returns, for example, for 100-year returns, rainfall of 109 mm / h is expected in the first 15 minutes of the event.